Mills for sale : the way ahead - D'Monte, Darryl (Mumbai : [Published by J.J. Babha for Marg Publications on behalf of the National Centre for the Performing Arts], 2006)
Contributed articles on the use of land on which cotton mills existed for real estate development in Bombay, India.
"This special project has been financially supported by the Sir Ratan Tata Trust"--P. 6.
Includes bibliographical references.
Keywords: Land use -- Government policy -- India -- Mumbai; Land use -- Government policy -- India -- Mumbai -- Pictorial works; Real estate development -- India -- Mumbai; Real estate development -- India -- Mumbai -- Pictorial works; City planning -- India -- Mumbai; City planning -- India -- Mumbai -- Pictorial works; Cotton textile industry -- India -- Mumbai; Cotton textile industry -- India -- Mumbai -- Pictorial works